Accuracy of diffusion-weighted magnetic resonance imaging in diagnosing malignant musculoskeletal tumours (Bangabandhu Sheikh Mujib Medical University Journal, 2024)
Background: Conventional magnetic resonance imaging (MRI) lacks specificity for differentiating several tumours. Combining advanced techniques like diffusion-weighted imaging (DW-MRI) with conventional MRI may enhance diagnostic accuracy. However, we do not have such data for Bangladeshi patients. This study aimed to examine the diagnostic accuracy of apparent diffusion coefficient values obtained by DW-MRI.Methods: A cross-sectional study was conducted from July 2022 to June 2023 in the Department of Radiology and Imaging, Bangabandhu Sheikh Mujib Medical University (BSMMU).  After collecting their baseline data, thirty-five patients with musculoskeletal tumours underwent DW-MRI and histopathology tests or fine needle aspiration cytology (FNAC). The apparent diffusion coefficient (ADC) values obtained by DW-MRI were examined for diagnostic accuracy against a standard of histopathology/FNAC.Results: According to the gold standard (histopathology/FNAC), there were 28 patients with malignancy, and 7 had benign tumours. Their mean age was 33 (standard deviation, 17) years (range, 4 to 74 years). The mean ADC value was 0.86 ± 0.30×10-3 mm2/s. The malignant musculoskeletal tumour group had significantly lower ADC (0.79 ± 0.24 ×10-3 mm2/s) compared to the benign tumour group (1.15 ± 0.37×10-3 mm2/s.) (P = 0.04). The DW-MRI ADC categories correctly diagnosed 27 malignant and five benign tumours using a cut-off value of ≤ 1.1×10−3 mm2/s. DW-MRI had a sensitivity of 96.4% and a specificity of 71.4%. Diagnostic accuracy was 91.4% for detecting malignant musculoskeletal tumours.Conclusions: Malignant musculoskeletal tumours have lower DW-MRI-derived ADC levels, demonstrating good diagnostic accuracy. However, a larger and more representative sample is needed before it is recommended for clinical practice.